KEABSAHAN JUAL BELI SEX TOYS PADA LOKA PASAR (MARKETPLACE) - Nabila Husniyah Susanto; Nynda Fatmawati Ocatrina (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
By using basic analysis on statutes or other legal documents.Buying and selling sex toys, on the other hand, is not a prohibited item and an illegal act if done in accordance with applicable law or in a specific manner and location.In the implementation of the sale and purchase transaction agreement, sex toys are deemed not to meet the legal requirements in Article 1320 of the Civil Code, including several legal reasons and the ability to conclude an agreement. The legal consequences of buying and selling sex toys are deemed not to meet the legal requirements in Article 1320 of the Civil Code, including several lawful reasons and the ability to conclude an agreement. The government is to make regulations and control sex toys and the sale and purchase of sex toys which have been circulating and being traded freely and without permission. Can be used as a basis for a marketplace platform in the implementation of the system, it is necessary to update or filter access so that commodities with certain criteria cannot be accessed by anyone. so that they can pay more attention to the good and bad impacts for business actors and consumers in buying and selling sex toys in the marketplace